2020
DOI: 10.3389/fimmu.2020.01882
|View full text |Cite
|
Sign up to set email alerts
|

Control of Gut Inflammation by Modulation of Purinergic Signaling

Abstract: Inflammatory bowel disease (IBD) is a serious inflammatory condition of the gastrointestinal tract. Crohn's disease (CD) and ulcerative colitis (UC) are two of the most common IBD manifestations and are both associated with unfettered inflammation, often refractory to conventional immunosuppressive treatment. In both conditions, imbalance between effector and regulatory cell immune responses has been documented and is thought to contribute to disease pathogenesis. Purinergic signaling is a known modulator of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Inflammation is commonly observed in many pathogenic conditions including infection, acute organ injury, and chronic organ dysfunctions [46][47][48][49][50][51][52][53][54]. Initially intended as a response to help resolve tissue injury, inflammation could become excessive and uncontrolled, which leads to further tissue injury and, occasionally, systemic inflammation [55][56][57][58][59]. For example, uncontrolled alveolar epithelial inflammation results in ARDS [1,16,60,61], which is the common and main cause of death in COVID-19 [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is commonly observed in many pathogenic conditions including infection, acute organ injury, and chronic organ dysfunctions [46][47][48][49][50][51][52][53][54]. Initially intended as a response to help resolve tissue injury, inflammation could become excessive and uncontrolled, which leads to further tissue injury and, occasionally, systemic inflammation [55][56][57][58][59]. For example, uncontrolled alveolar epithelial inflammation results in ARDS [1,16,60,61], which is the common and main cause of death in COVID-19 [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the pharmacological manipulation of purinergic signalling represents a viable way to counteract several gastrointestinal diseases [50]. For example, purinergic-mediated strategies as adjunctive treatments were used to correct immune dysregulation in inflammatory bowel disease (IBD) patients [51]. Whether the P2 receptor was modulated by miRNAs in gastrointestinal diseases remain to be studied.…”
Section: Purinergic Signalling Modulated By Mirnas In Gastrointestinal Diseasesmentioning
confidence: 99%
“…However, since CD39 also plays an important role in tumor development and progression (99,(118)(119)(120)(121) and inhibition of effector immune responses against pathogens (99,122,123), the safety of long-term treatments aimed at restoring the levels of this ectoenzyme in the context of autoimmune diseases should be considered and carefully evaluated. A2A receptor agonists that enhance the adenosinergic signal might also have a role in restoring immunotolerance by reconstituting the purinergic milieu (41).…”
Section: New Immunotherapiesmentioning
confidence: 99%
“…Extracellular nucleotides and nucleosides are strong modulators of T-cell immunity ( 40 ). Mounting evidence links alterations of purinergic signaling with the immunological dysfunction present in autoimmune conditions ( 41 ). Both Treg and Th17-cells obtained from AIH patients express low levels and impaired activity of the immunoregulatory ectoenzyme CD39 ( 42 , 43 ).…”
Section: Introductionmentioning
confidence: 99%